Assessment of Global Geopotential Models for Modelling Malaysia Marine Geoid - Md Din, Ami Hassan; Yahaya, Noor Anim Zanariah; Omar, Abdullah Hisam; Mohammad Yazid, Nornajihah; Mohamad Abdullah, Nazirah; Pa'suya, Muhammad Faiz; Abdul Wahab, Mohamad Ikbar (International Journal of Integrated Engineering, 2022)
The evaluation towards global geopotential models represents a significant part in modelling the localised Marine Geoid. The marine geoid provides the vertical reference information in Marine Spatial Data Infrastructures (MSDI) development response to United Nations Sustainable Development Goals 14 for the sustainable development in marine environment. The main purpose of this study is to select the best model from both combined missions and satellite-only missions for the Malaysian region. The gravity anomaly field from 30 global models were exclusively calculated over the selected study area within 11 years period-time. Afterwards, each dataset was extracted from the ICGEM server to evaluate with the airborne-derived gravity anomaly from the Department of Surveying and Mapping, Malaysia. The internal accuracy, root mean square error (RMSE) and differences between every model and airborne data were computed. The result indicates GGM-derived gravity anomaly for the best combined mission is GECO with RMSE of 8.44 mGal and the standard deviation value of 28.034 mGal. While, the model from Gravity field and steady state Ocean Circulation Explorer (GOCE) namely, the GO_CONS_GCF_2_DIR_R5 is the best for the satellite-only mission with RMSE of 17.43 mGal and the standard deviation value of 22.828 mGal. As a conclusion, GECO model is preferred as the best fit for determining the marine geoid as it has the lowest RMSE value between both mission and the maximum degree of 2109o coverage. The finding can assist in development of marine geoid for modelling precise surface elevation.